DEEPSEAMINERALS - Lim, Anna (2022)
As the need for critical minerals is now expected to be greater than the supply from the mining industry and recycling, Norway is in an excellent position to become a leader in the exploration for deep-sea minerals. The race has started, and at this conference, we will address challenges and opportunities that lie ahead.